Parameterization of flow intermittency and river styles in two hydrographic basins in the semiarid region of Paraíba - Jeferson Mauricio Rodrigues; Jonas Otaviano Praça de Souza (Revista Brasileira de Geomorfologia, 2025)
This study parameterizes the behavior of intermittent rivers under similar morphoclimatic conditions in the Brazilian semi-arid region, focusing on the Paraíba and Piranhas River basins, impacted by SFIP. Methodologically, the base flow index (BFI) and the analysis of river styles (River Styles - RS) were integrated to characterize the perenniality and intermittency of rivers and to understand the geomorphological variability of river stretches. The BFI indicated that both rivers have perenniality of less than 5%, with the Paraíba River exhibiting a higher intermittency than the Piranhas River, corroborating analyses of frequency and duration of flow. The fluvial styles identified include confined (rocky and gravel) and partially confined stretches, with variability in geological and morphological controls. The fluvial style matrix revealed distinctive attributes, such as bed texture and connectivity, emphasizing the influence of hydrogeomorphological dynamics on fluvial stretches. The results contribute to the understanding of intermittent rivers in semi-arid environments, providing subsidies for hydrological analysis and water resources management in similar regions. Thus, this work is important to deepen studies in semi-arid river environments by providing a qualitative and quantitative proposal for analyzing intermittency and river behavior.